Binding of platinum derivative, oxaliplatin to deoxyribonucleic acid: structural insight into antitumor action. Issue 14 (22nd September 2019) - Ray, Bhumika; Gupta, Bhumika; Mehrotra, Ranjana
Abstract: Platinum-derived chemodrugs constitute an active class in cancer therapeutics. Besides being potent against various solid tumors, oxaliplatin has been recognized as the first platinum compound to be approved for the treatment of colorectal cancer. Structurally, oxaliplatin consists of a platinum metal complexed to oxalate and diaminocyclohexane (DACH) and exert its anticancer action by inhibiting DNA replication and transcription. The present study highlights the binding properties of oxaliplatin with calf thymus DNA using spectroscopic methods to comprehend its binding mechanism at molecular level to overcome associated cellular resistance and side effects. Attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopic outcomes confirm that oxaliplatin is a covalent binding agent and also provide sequence specificity in DNA molecule. Infrared spectral results further indicate that oxaliplatin alkylates purine nitrogenous bases majorly guanine residues (G) in the major groove via formation of either interstrand or intrastrand guanine–guanine d (GpG) and guanine–adenine d (GpA) (N7 position) crosslinks accompanied with a slight external binding to sugar–phosphate backbone. Again, circular dichroism (CD) spectroscopic results suggest subtle conformational changes in DNA molecule due to its complexation with oxaliplatin and duplex attains an intermediate conformational state, having characteristics of both B- and C-forms. Further, a moderate binding strength of 4.12 ± 0.2 × 10 4 M −1 for the interaction has been estimated via ultraviolet–visible spectroscopy. The inferences obtained from these investigations are encouraging and can form the basis for further exploration in the field of rational drug development based on platinum compounds possessing preferential binding for nucleic acid with improved competence. Communicated by Ramaswamy H. Sarma